Influence of bioslurry on the growth, yield and nutritional status of Indian Spinach - Amit Kumar Basunia (Journal of the Bangladesh Agricultural University, 2020)
The fertility and productivity of cultivable land has been declining day by day due to imbalance use of chemical fertilizers. Therefore, a pot experiment was conducted at the shade house of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from February, 2018 to March, 2019 in order to evaluate the influence of bioslurry on growth, yield and nutritional status of Indian spinach. The two-factor experiment comprised two varieties of Indian spinach viz., BARI Puishak-1 and BARI Puishak-2 and five levels of bioslurry namely no bioslurry and no fertilizer (control), 10, 15, 20 ton/ha bioslurry and recommended dose of inorganic fertilizers. The experiment was laid out in a randomized complete block design with five replications. Results showed that BARI Puishak-2 performed superior in respect of growth, yield contributing traits and nutritional constituents as compared to BARI Puishak-1. In case of treatments, the highest value of vine length, leaf number, branches per plant, leaf area, dry mater, yield and nutrients (phosphorus, potassium, sulfur, calcium, and sodium) were achieved from the recommended inorganic fertilizers while those parameters were the lowest in control plants. The combination of BARI Puishak-2 with recommended inorganic fertilizers showed the highest vine length, leaf number, number of branch per plant, stem diameter, leaf area, dry mater, yield and nutritional status, while those parameters were lowest in BARI Puishak-1 with control treatment. However, the results of the study revealed that bioslurry 20 ton/ha showed nearly similar performance as recommended inorganic fertilizers. Since, bioslurry contains sufficient amount of nitrogen, potassium and phosphorous, therefore, it could be the effective alternative sources of nutrients instead of chemical fertilizers for sustainable and eco-friendly production of Indian spinach. [J Bangladesh Agril Univ 2020; 18(2.000): 379-387]